Монгол аман зохиол, уран зохиолын харилцаа холбооны асуудалд: On the issues of relationship between Mongol folklore and literature - С., Дулам (Mongolian Studies, 2023)
In this article, the author examines the relationship between tradition and continuity of oral and written literature by several aspects that might be useful for the further studies by young researchers. The article details the relationship between Mongol folklore and literature. - It is necessary to study the relationship and continuity of Mongol folklore and literature from the genres to the descriptive level. - There will be interesting results if this study analyzes by either author or work itself. - There will be possibility of having complete study if this study ties to oral tradition, culture and ancient and classical literatures.